Preparação, caracterização e otimização de biocompósitos poliméricos comestíveis reforçados com fibras vegetais - Otoni, Caio Gomide (2017)
The ever-growing environmental concern arising from the unrestricted exploitation of fossil raw materials for the massive production of non-biodegradable materials, guided by the rapid increase in the world population as well as in the demand for foodstuffs, encourages research on alternative materials from renewable sources. Herein, edible biocomposites based on peach puree or carrot processing waste (CPW) were produced. Hydroxypropyl methylcellulose (HPMC) and cellulose fibers were added to play ligand and mechanical reinforcement roles, respectively. Previously, the film-forming components were comprehensively studied separately. The effects of HPMC chemical structure were investigated in order to choose a grade – Methocel® E4M – that leads to suitable physical-mechanical performance. Cellulose fibers were miniaturized by high-pressure microfluidization and its dispersion within the HPMC matrix was optimized through a central composite design (CCD). Seven microfluidization cicles were found to be ideal for the mechanical reinforcement of the matrix. Once the behaviors of miniaturized cellulose fibers, peach puree, and CPW in the HPMC matrix were elucidated, ternary mixture designs were carried out to set up correlations among biocomposites’ formulations and their mechanical properties. Optimized formulations were used to produce (i) biodegradable biocomposites featuring suitable physical-mechanical properties for packaging applications – using CPW, HPMC, and cellulose fibers – and (ii) edible bioplastics having unique sensory and nutritional characteristics by means of combining peach puree and HPMC. Finally, the production protocols of both materials were successfully scaled-up towards a pilot scale through a continuous casting approach, being the influence of the processing protocols on materials’ properties investigated.